Polymerase chain reaction for the detection of canine parvovirus in faeces of Dogs - Josemi Mathew (Department of Microbiology, College of Veterinary and Animal Sciences, 2004)
A study was undertaken to compare the ability of haemagglutination (HA), polymerase chain reaction (PCR) and seminested PCR for the diagnosis of canine parvovirus (CPV) infection by detecting CPV from faecal samples of clinically suspected dogs. Characterization of vaccine strain and field strains of CPV was performed by restriction enzyme analysis (REA) in this study. Attempts were made to isolate CPV from faecal samples in MDCK cell line. One hundred and twentysix faecal samples were collected from dogs suspected for CPV infection and 40 faecal samples were also collected from normal healthy non-vaccinated as well as vaccinated dogs after 15 days of vaccination, that were brought to veterinary hospitals attached to KAU. All the samples were screened by HA, PCR and seminested PCR to detect CPV. No significant difference in HA titre could be appreciated on comparing the titre using PBS, pH 7.2 and PBS – BSA as diluents. The haemagglutination reaction by CPV was found to be favoured by a slightly acidic pH in the range of 4.0 to 6.0. Chloroform treatment of faecal samples had no influence on HA titres above 5 log2. Among 126 faecal samples screened, 43.65 per cent, 61.11 per cent and 73.81 per cent were tested positive for CPV infection by HA, PCR and seminested PCR respectively. Therefore, seminested PCR was found to be a more sensitive and specific method over HA and PCR for the early diagnosis of CPV infection. All the faecal samples from healthy non-vaccinated and vaccinated dogs after 15 days of vaccination were tested negative by HA, PCR and seminested PCR. Restriction enzyme analysis using HinfI, Rsa I and Sau 961 revealed no difference in the fragment length patterns between CPV vaccine strain and field strain. Attempts to isolate CPV from faecal samples in MDCK cell line were found unsuccessful. The occurrence of CPV infection among non-vaccinated dogs was found to be higher than that of vaccinated dogs. Vaccine failure was also observed after MLV vaccination. The distribution of CPV infection was highest among dogs between two to four months of age. Breed-wise distribution of CPV infection showed highest distribution in German shepherd dogs when compared to other breeds. Most of the cases of CPV were noticed during February and July in the year 2003 and during March to June in the year 2004.